DYNAMIC FLTIX DISPLAY OF TRANSFORMER (Journal of Engineering, 2002)
This work presents procedures to utilise the finite element results of magnetic flux density vector to create animation tile which displays rapidly successive frames, prepared by postprocessing ,leading to the effect of moving flux to the viewer .The method is applied to 2-D transformt or  model showing excellent animation effect of the alternating flux in both the core area and the leakage flux area. The method is useful in analysis as the dynamic flux monitoring gives more details than static display. The method can be used to produce instructional materials giving the student an impression of the natural behaviour of the electromagnetic devices.